Estimation of the gene pool of the CIMMYT collection winter bread wheat on presence of the Lr 34 gene - N. N. Vozhzhova; О. S. Zhogaleva; А. Yu. Dubina; N. T. Kupreyshvili; T. G. Derova; S. V. Podgorny (Зерновое хозяйство России)
Nowadays in Russia and in the world, the problem of improving food security is becoming more and more urgent. One of the main crops grown worldwide is winter bread wheat. Varieties resistant to main leaf diseases can produce large grain yields. Thus, the study and identification of resistance genes are of great importance. The purpose of the current work was to estimate the gene pool of winter bread wheat from the CIMMYT collection (Mexico) according to the age brown rust Lr 34 resistance gene. In the study of collection samples, there have been used such methods as DNA extraction using CTAB, PCR, electrophoresis on agarose gels. As a result of the study, there has been identified a presence of a functional allele of the Lr 34 gene in 146 winter bread wheat samples out of 411 studied ones (sets 20th IWWYT-SA, 21th IWWYT-IRR, 25th FAWWON-IRR, 25th FAWWON-SA). There have been identified three samples with a heterozygous allelic state of the Lr 34 gene. There have been identified 232 samples with the non-functional Lr 34 gene allele. 30 winter bread wheat samples had no amplification of DNA fragments with the molecular marker csLV34, which means a significant microsatellite sequence variability for which the molecular marker was developed in their genotype. 121 out of 146 winter bread wheat samples with the functional brown rust Lr 34 resistance gene showed resistance in field conditions and in the infectious plots. The rest 25 samples with the Lr 34 gene belonged to the group of moderately resistant ones in the infectious plots. The identified 121 CIMMYT collection winter bread wheat varieties, with the Lr 34 gene possessing a resistant type of pathogen damage response (for example, 9919, 9921, 9928, 9809, 9811, 9812, 23, 24, 30, 262, 265, 266, etc.) have been recommended for use in leaf rust resistance pyramiding in future breeding programs.